ANALISIS KETERLIBATAN PERILAKU SISWA DALAM PEMBELAJARAN BAHASA INDONESIA PADA KELAS II SDN SEMPER BARAT 11 - Teresa Cinta Cahyadewi; Otib Satibi Hidayat; Uswatun Hasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Student behavioral engagement is one of the key indicators in assessing the quality of the learning process, as it reflects the extent to which students actively participate in classroom learning activities. This study aimed to analyze students’ behavioral engagement in Indonesian language learning in grade II of SDN Semper Barat 11. This study used a qualitative descriptive approach. The participants were 32 students of class II D. Data were collected through non-participant observation and documentation during two learning meetings. The data were analyzed using the Miles and Huberman analysis model. The results showed that students’ behavioral engagement had not appeared evenly among all students. Most students showed good attention, followed the teacher’s instructions, and were involved in completing learning tasks during the lesson. However, in the indicator of active participation, especially asking questions, students’ engagement was still low because no students asked questions during the observation. In addition, several students consistently showed low engagement in almost all observed indicators. Based on the findings, it can be concluded that students’ behavioral engagement in Indonesian language learning was still dominated by participation that appeared when students were directed by the teacher and had not fully emerged from students’ own initiative. Therefore, teachers need to provide more opportunities for students to ask questions, express opinions, and actively participate during the learning process.